EUROPEAN PUBLIC PROSECUTOR’S OFFICE - Bugarski, Tatjana; Pisarić, Milana (Zbornik radova Pravnog fakulteta u Novom Sadu, 2019)
As the European Union loses a significant part of the financial resources per year due to the criminal offense of fraud and similar criminal offenses committed against financial interests of the Union, there has been a presumption that a body competent for investigation of such illegal conduct and criminal prosecution of offenders should be established at supranational level. For this reason, the Commission of the European Union presented the Proposal for the Establishment of the European Public Prosecutor's Office as a body authorized to investigate criminal offenses affecting the financial interests of the European Union and to criminalize the perpetrators of these offenses. Following the multi-annual negotiations between the member states and the institutions of the Union and the adaptation of the initial text, Regulation implementing enhanced cooperation on the establishment of the European Public Prosecutor’s was adopted in October 2017. As the first European Union body competent to make decisions in relation to individuals in the sensitive field of criminal law, the establishment of the European Public Prosecutor's Office constitutes a significant moment in the history of the criminal law of the Union. However, expert and scientific analyzes point out that this potentially revolutionary step carries with it quite complicated and far-reaching consequences, and it is controversial whether and to what extent such a supra-national body, with such a predicated structure and competences, will contribute to the suppression of criminal offenses affect the financial interests of the Union.